STRUKTUR DAN KOMPOSISI JENIS TUMBUHAN PADA HUTAN RAKYAT TONGKONAN LEMBANG TURUNAN KECAMATAN SANGALLA KABUPATEN TANA TORAJA - Wahyudi, Wahyudi; Sudiyanto, I wayan; Nirawati, Nirawati (Jurnal Eboni, 2024)
Tongkonan community forest has an important role in Torajanese livelihood. The forest could serve daily needs and diverse ceremonial materials for local people. The existence of this forest also has an ecological function in soil and water preservation. This research aims to study the structure and composition of vegetation in tongkonan community forest and determine the useful plant species for the local people. The research method was done by counting and identifying plants in plot samples for the study of the plant community structure and composition and brief interviews with the local people to reveal the purpose of the plant species. There are 30 plants species that found in plot samples belongs to 28 genera and 18 families. According to the family level, the dominant plant species in observation were Fabaceae (14,28 %) and Myrtaceae (10,71 %). Pine tree (Pinus merkusii) had the highest basal area of 7163.054 cm2 and the species with the highest Important Value of 35.486 %. Several species, however commonly cultivated in this area such as kakao (Theobroma cacao) and kopi (coffea robusta). Generally in the village, around 35 plant species (51,47 %) are used as a source of food, while 39 species (57,35 %) are used for other purposes, such as traditional medicine, firewood, materials for tools and crafting, and ornamental plant species.